Możliwości oceny cechy lokalizacji nieruchomości jako elementu rynku lokalnego, w oparciu o dane z rejestrów geodezyjnych = Possibilities of location evaluation for property as an element of local market, on the basis of land register data - Zyga, Jacek (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article is a part of wider research on practical usefulness of public land registers, creating governmental real estate?s database, in several tasks connected with property appraisal. It shows results of the mentioned above analysis of usefulness of data, contained in land register, property price and value register and other public registers directly connected with real estate's, in evaluating of generally grasped location - key parameter of properties.
Keywords: lokalizacja nieruchomości; wartość nieruchomości; ewidencja gruntów i budynków; property location; cadastre; land register